Cyber Crime in Renewing The ITE Law to Realize The Goals of Legal Justice - Adwi Mulyana Hadi (Journal of Law, Society, and Islamic Civilization, 2024)
Cybercrime in Indonesia is currently regulated by the Electronic Information and Transactions (ITE) Law, but it is considered inadequate to accommodate the various developments of cybercrime, so that renewing the ITE Law is important. The renewal of the ITE Law is needed to provide legal certainty and adequate protection for the public, as well as to improve the effectiveness of law enforcement against cybercrime perpetrators. The purpose of this study is to evaluate the regulation of cybercrime in the ITE Law with a focus on justice and victim protection aspects as well as to identify matters that need to be regulated and refined in the renewal of the ITE Law related to cybercrime. This study uses a normative method with a statutory and conceptual approach, analyzing primary, secondary and tertiary legal materials related to cybercrime. Data were collected through literature study then analyzed descriptively qualitatively to formulate problem solving recommendations based on the results of the analysis. The results of the study illustrate that the regulation of cybercrime in the current ITE Law is still considered weak in providing justice and protection for victims. This can be seen from the limited definition of cybercrime, unclear elements of criminal acts, weak victim protection, as well as excessive and disproportionate criminal provisions. Therefore, renewing the ITE Law is necessary to expand the definition of cybercrime, refine the formulation of criminal acts, increase victim protection, adjust criminal sanctions, and regulate recovery systems for aggrieved parties in order to achieve better justice and legal certainty.